Genotypes of Papillary Thyroid Carcinoma With High Lateral Neck Metastasis in Chinese Population - Guo, Wei; Huang, Junwei; Shi, Taiping; Duan, Hanyuan; Chen, Xiaohong; Huang, Zhigang (Frontiers in Oncology, 2022)
Papillary Thyroid Carcinoma (PTC) is one of the most commonly diagnosed cancer types in China, characterized by its early age at diagnosis and high 25-year survival rate. Distinct mutational patterns in PTC have been linked to activation of the mitogen-activated protein kinase (MAPK) signaling pathway. To explore the clinical significance of genomic variation patterns in Chinese patients with thyroid carcinoma, we investigated the genomic variants in 83 PTC cases with complete clinical records. The mutational patterns were evaluated using a 688-gene panel which covered known driver genes in PTC tumorigenesis, and featured genetic markers in various PTC-related pathways. We evaluated the relationship between mutational landscape and various clinical information in PTC patients with lateral lymph node metastasis. BRAF V600E was the most common mutation. Mutations in NF1, CDC27, PMS2 and PPP4R2 were more common in men, and mutations in NF1, PMS2 and TERT were related to lateral lymph node metastasis. According to the clustering of mutational patterns, we show that the underline driving mechanisms in lateral lymph node metastasis can be divided into two major groups (BRAF-TERT pathway, and NF1-PMS2 pathway). When combined with the TERT mutations, the BRAF mutation group was prone to lateral lymph node metastasis, particularly in elderly women. The NF1 mutations usually co-existed with PMS2 mutations, and this group included more men and young patients who had a high tumor mutational burden and lateral lymph node metastasis rate.